'You can make change happen': Experiences of emergency medicine leadership in the Pacific. (18th November 2021) - Phillips, Georgina; Shailin, Shivani; Lee, Dennis; O'Reilly, Gerard; Cameron, Peter
Abstract: Objective: We sought to explore the activities, responsibilities and experience of leadership from Pacific emergency medicine (EM) doctors. Additionally, we explored knowledge, attitudes, leadership gaps and training insights for individual clinicians, and from a Pacific regional perspective. Methods: This was a qualitative study using in‐depth, semi‐structured interviews of invited Pacific EM doctors occupying a leadership role in their countries. Data were recorded, transcribed and triangulated with written field notes. Whole interviews and responses per topic were analysed using data‐platform‐based and manual methods. Inductive and deductive coding and thematic content analysis was performed in partnership with Pacific co‐researchers to determine overall meaning. Monash University granted ethics approval. Results: Twelve doctors participated (11 verbal, one written response), representing six different Pacific Island countries. Four key themes were identified which reflected both the individual agency of the Pacific EM doctors and how their experience was constituted by others; professional identity and style; nurturing relationships and building solidarity; growth through experience, education and challenge; and progress and precarity. Pacific EM leaders perform clinical, management, advocacy and education tasks, and build their capacity and resilience through leadership training. They have a strong desire for regional solidarity and networking. Conclusions: Pacific EM doctors embrace leadership in their home countries and collaborate to drive positive change, build teams and gain recognition. As pioneers and advocates for EM, they bear high responsibility and risk burnout. These findings can inform future targeted leadership training and contribute to building Pacific regional networks for career sustainability and specialty advancement. Abstract : We interviewed 12 Pacific emergency medicine (EM) doctors to explore their activities, responsibilities and experience of leadership, from both an individual and regional perspective. Pacific EM doctors modelled a supportive, collaborative style of leadership that balanced approachability with authority and was nurtured through interpersonal and regional solidarity. Targeted leadership training, supportive relationships and resource sharing will enable future regional networking, specialty development and sustainable individual leadership for EM doctors across the Pacific.